STUDI KELAYAKAN BISNIS BERDASARKAN ASPEK PASAR STUDI KASUS PADAUCOK DURIAN MEDAN - Riezky Bagus P; Afryan Syahputra; M. Rizky Erlangga (Cahaya Ilmu Bangsa, 2025)
This article discusses the importance of business feasibility study with a focus on market analysis as a crucial aspect in decision-making to start a business, particularly in Medan, Indonesia. The methodology used in this research is a qualitative approach with a descriptive method, using secondary data obtained through literature studies of relevant documents, journals, and articles. The case study analyzed is a durian market managed by Duren Ucok, which shows a positive trend in durian consumption among local people and tourists. The results identified two main segments of consumers, namely local people who buy durian in bulk and tourists who seek a distinctive culinary experience. Duren Ucok's diverse product offerings, including durian preparations, create a unique appeal to consumers. The research conclusions emphasize that in-depth market analysis and an understanding of consumer preferences are critical to formulating effective marketing strategies. Duren Ucok has successfully created a strong brand image and demonstrated that innovation and adaptation to market trends can increase business competitiveness. Therefore, a thorough market analysis is key to business success in a dynamic environment. Keywords: Business Feasibility Study, Market Aspects, Market Analysis, Market Segmentation